Is Airbnb a Sharing Economy Superstar? Evidence from Five Global Cities. Issue 4 (2nd October 2018) - Crommelin, Laura; Troy, Laurence; Martin, Chris; Pettit, Chris
Abstract: The "sharing economy" concept has been embraced by governments, entrepreneurs and commentators as delivering new forms of opportunity for local and national economies. Accommodation-sharing platform Airbnb is often considered a sharing economy exemplar, and has promoted itself as helping middle-class residents to gain and retain a foothold in expensive housing markets. This narrative is particularly salient in "global cities", where poor housing affordability and high tourist demand inevitably coexist. However, critics claim many Airbnb listings are actually permanent short-term rentals. Thus, instead of enabling new efficiencies in the use of housing assets and providing financial security for existing residents, Airbnb may be a variation on an old theme: removing properties from the market for long-term rental or purchase. This paper has three aims: it critically interrogates the sharing economy concept in relation to Airbnb; it reviews the regulatory responses to Airbnb in five global cities; and it examines Airbnb listing data in each city. Ultimately, the paper argues that while some Airbnb listings do fit the sharing economy narrative, others are part of the traditional economy of short term letting. Policy makers need to recognise the different impacts of these uses in their responses to Airbnb and the sharing economy.